Competency Models for Advancing Transformation in Account Representative Roles - Sirait, Deny Sahat Mangitua (International Journal of Industrial Engineering, Technology & Operations Management, 2023)
This study endeavors to ascertain and pinpoint the essential competencies for Account Representatives to orchestrate institutional transformation within the Directorate General of Taxes. Using the delayering program, the organization aims to transition employees from structural roles to functional positions. The study was conducted across several tax service offices, ensuring representation in alignment with the diverse tax office types within the North Sumatera I Regional Office. Employing the Analytic Hierarchy Process (AHP) methodology, the study meticulously analyzed the prioritization of competencies delineated by the National Civil Service Agency across three distinct categories: managerial, sociocultural, and technical competencies, soliciting respondent feedback. This approach facilitated a comprehensive examination of the competencies requisite for Account Representatives to shape institutional transformation within the Directorate General of Taxes. The strategic implementation of the delayering program aims to foster a transition from structural to functional roles for its employees, reflecting a commitment to adaptability and efficiency within the evolving tax landscape.